International guidelines for the management ofANCA-associated systemic vasculitides - T. V. Beketova (Современная ревматология, 2019)
The paper deals with international guidelines for the management of antineutrophil cytoplasmic antibody (ANCA)-associated systemic vasculitides (SVs) that are a group of severe life-threatening immune-mediated diseases. This group includes granulomatosis with polyangiitis (Wegener's granulomatosis), microscopic polyangiitis, and eosinophilic granulomatosis with polyangiitis (Churg-Strauss). ANCA-associated SVs (ANCA-SVs) are an important problem of practical rheumatology. The guidelines for the management of ANCA-SV, which were published by the International Group of Experts, which summarize modern scientific achievements and international clinical experience, currently remain the basis for treatment of these diseases.